A Correlation Between Education And Early-Age Pregnancy With The Incidence Of Chronic Energy Deficiency (Ced) Among Pregnant Women In The Working Area Of Karya Sakti Health Center, Musi Rawas - Sulitiawati, Niken; Anissa, Kintan; Aulia Umami, Desi (Multidisciplinary Journals, 2024)
Chronic Energy Deficiency (CED) is a condition of nutritional deficiency in pregnant women. The issue in this study is the increase in CED cases at Lingkar Barat Health Center, which rose by 10.02% from 3.68% in 2016 to 14.7% in 2017. This study aims to determine the correlation influencing CED among pregnant women at Karya Sakti Health Center, Musi Rawas. This research is an analytic survey with a cross-sectional approach. The sample size is 44 pregnant women.The study was conducted using univariate and bivariate analyses. The results showed that education (p=0.016) and early-age pregnancy (p=0.033) were correlated with the incidence of CED. It is hoped that the health center will enhance programs to manage CED in pregnant women and perform early detection of factors causing CED.Midwives are encouraged to improve their services to pregnant women by increasing knowledge through updated literature and providing direct education to pregnant women about the nutritional needs during pregnancy. They should also offer recommendations on foods rich in folic acid and iron to prevent anemia caused by CED in pregnant women.